2019
DOI: 10.1016/j.rmed.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Mold burden in house dust and its relationship with asthma control

Abstract: Some evidences indicate that exposure to molds or their products can be relevant for the loss of asthma control. Thus, we measured the mold burden present inside houses of subjects with asthma, and evaluated its relationship with asthma control. Methods: Markers of asthma control in adult patients residing in Mexico City were evaluated through questionnaires and spirometry. Dust was collected from the patients' houses and its fungal content was determined by mold specific quantitative PCR (MSQPCR) for 36 funga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 58 publications
0
17
0
Order By: Relevance
“…Moreover, a number of different types of mold exist and the F I G U R E 6 Maximum mold index over the course of a year on the inner wall surface conditions for mold growth differ from one incidence to another. 31,80 This study, as well as most epidemiological studies on building dampness, is based on self-reported information from questionnaires, in which recall bias may exist. 7 Only a few studies have assessed household dampness by inspection or in situ measurements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of different types of mold exist and the F I G U R E 6 Maximum mold index over the course of a year on the inner wall surface conditions for mold growth differ from one incidence to another. 31,80 This study, as well as most epidemiological studies on building dampness, is based on self-reported information from questionnaires, in which recall bias may exist. 7 Only a few studies have assessed household dampness by inspection or in situ measurements.…”
Section: Discussionmentioning
confidence: 99%
“…We attributed such differences to the various methods and measurements adopted in these researches, with variance in self‐reporting, inspection, measurement, and simulation. Moreover, a number of different types of mold exist and the conditions for mold growth differ from one incidence to another 31,80 . This study, as well as most epidemiological studies on building dampness, is based on self‐reported information from questionnaires, in which recall bias may exist 7 .…”
Section: Discussionmentioning
confidence: 99%
“… Dong et al (2020) showed that treatment with Gu–Ben–Fang–Xiao Decoction (GBFXD) increased the abundance of Lachnospiraceae in asthmatic mice, which consequently led to elevated levels of short-chain fatty acids. Patricia et al found that the abundance of Epicoccum was negatively associated with male asthma patients ( Segura-Medina et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact carpets concentrate more dust than non-carpeted floors; thus, for example, Heinrich et al (2003) [ 41 ] have standardized approaches for vacuuming carpeted (dusting 1 m 2 ) and non-carpeted floors (dusting the whole room). NHANES did not test for Alternaria or Cladosporium allergens, or black molds (e.g., Stachybotrys chartarum ), which are increasingly acknowledged allergenic sources and may be associated with worse asthma control in some cases (Segura-Medina et al, 2019) [ 42 ], this being another limitation of our study. A cluster analysis that Mendy et al (2020) [ 43 ] used would have assessed real life exposures.…”
Section: Discussionmentioning
confidence: 99%